Relação família/escola e o processo de aprendizagem de alunos do 2º ano do ensino fundamental em uma escola pública de Altamira-PA - LOPES, Pamela Daniele dos Santos Ferreira (2021)
Family participation in the schooling process contributes to learning. Considering the relevance of this theme, the purpose of this study was to understand how the family / school relationship can influence the learning process in reading children from the 2nd year of elementary school in a public school in Altamira-Pará-Brazil. It is an empirical study, with a qualitative approach, carried out with one teacher, and four mothers / students dyads. The instrument used was a semi-structured questionnaire with 5 questions. The results showed that two mothers participated effectively in the schooling process, and the children had a satisfactory income, while the two mothers who did not participate, the children had a learning deficit and were disapproved. The conclusion was that family participation in school and the family / school relationship influence children's learning. The more satisfactory family participation in the school, the lower the learning difficulties of the children.